As configurações subjetivas de docência e suas transformações no decorrer da trajetória profissional - RESQUE, Marciléa Serrão (Universidade Federal do Pará, 2019)
In this article, we present a review of a doctoral research, in which we aim to understand the subjective configurations of teaching and its transformations during the professional career of a professor of science and biology. Based on the historical-cultural perspective of González Rey's Theory of Subjectivity. Based on qualitative epistemology, we present a case study, organized from the information constructed through phrases complement, open questionnaire and individual interview. The results show that different configurations of subjective senses of teaching are produced along the professional path and these are deeply linked to their social interactions, in the different contexts in which the teacher has transited since childhood. The adopted framework allowed to give visibility to the concrete subject, in its singular trajectory, which is usually disregarded in the generalizations that result from an approach of the teaching path by cycles.